Increasing Knowledge Translation Capacity in Low- and Middle-Income Countries: A Model for Implementation Research Training - Penkunas, Michael J.; Berdou, Evangelia; Chong, Shiau Y.; Launois, Pascal; Rhule, Emma L. M.; Allotey, Pascale (Frontiers in Tropical Diseases, 2021)
Most health professionals lack the training and expertise to translate clinical innovations into actionable programs. Even though some public health expert communities understand that even widely proven solutions need to be adapted to the demands and characteristics of diverse health systems and societies to be successful, such knowledge has yet to inform routine public health approaches and practices. Therefore, it should not be a surprise that the “know-do” gap between clinical innovations and their on-the-ground application that implementation research seeks to bridge is pervasive and enduring, particularly in low- and middle-income countries. This article draws on a study of implementation research training courses to highlight the various competencies needed to translate different types of knowledge into action, many of which are not adequately addressed in existing curricula. We utilized a four-phase modified Delphi methodology that included a review of the academic and grey literature, one-on-one interviews with experts, virtual dialogue series with key stakeholders, and peer review of the synthesized results. The resulting areas in need of further development include the ability of learners to work as part of a multidisciplinary team, engage various stakeholders, and communicate research findings to decision-makers. Based on these insights, it is argued that knowledge translation in implementation research is a multi-faceted, multi-level sensemaking and communication activity that takes place throughout the research and research-to policy-processes.